Comparative Studying of Human Cord Blood Components Antiviral Activity at Experimental Grippe Viral Infection - Onasenko, E. S.; Brovko, E. V.; Stepanyuk, L. V.; Ponomareva, V. L. (Problems of Cryobiology and Cryomedicine, 2008)
Comparative studying of human cord blood leucoconcentrate and its components antiviral activity was carried out. It was established that the highest inhibiting activity possessed human cord blood leucoconcentrate and plasma. This allows to assume their usage for grippe virus diseases prophylaxis. The further research of leucoconcentrate antiviral activity is necessary for final judgement its efficiency as a nonspecific antiviral protective preparation.